2019
DOI: 10.1021/acs.jpcc.9b00068
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of SiC Grain Boundaries to Oxidation

Abstract: Molecular dynamics simulations of dry oxidation of bicrystals with incoherent and coherent grain boundaries (GBs) in 3C–SiC are performed at 2000 K and the results are compared to oxidation of single-crystal SiC. Oxidation near incoherent GBs is found faster than that in single crystals and in coherent GBs, whereas oxidation of coherent GBs is comparable to that of single crystals. The accelerated oxidation near incoherent GBs is attributed to strain and the presence of under-coordinated Si within the GB regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 76 publications
4
14
0
Order By: Relevance
“…By exposing an unirradiated SiC to the supercritical water, Tan et al have found that incoherent GBs are more significantly corroded than the coherent ones [11]. These experimental results are consistent with our recent molecular dynamics (MD) simulations [12]. Specifically, we have previously shown that incoherent tilt GBs oxidize faster than the bulk SiC whereas coherent GBs do not.…”
Section: Introductionsupporting
confidence: 91%
See 4 more Smart Citations
“…By exposing an unirradiated SiC to the supercritical water, Tan et al have found that incoherent GBs are more significantly corroded than the coherent ones [11]. These experimental results are consistent with our recent molecular dynamics (MD) simulations [12]. Specifically, we have previously shown that incoherent tilt GBs oxidize faster than the bulk SiC whereas coherent GBs do not.…”
Section: Introductionsupporting
confidence: 91%
“…were randomly and uniformly inserted into a 40 Å vacuum region above the SiC surface; the corresponding gas pressure at 2000 K is ~552.5 MPa. Our simulated oxygen partial pressure is significantly higher than pressures used in dry thermal oxidation experiments, which is in the order of tens of kPa [12]. This high pressure used in our simulations is necessary to observe reactions on the time scales of MD simulations.…”
Section: Methodsmentioning
confidence: 93%
See 3 more Smart Citations